2004
DOI: 10.1002/ajh.20060
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin‐induced limb gangrene in the setting of lung adenocarcinoma

Abstract: A 53-year-old man with lung adenocarcinoma developed pulmonary embolism and bilateral popliteal venous thrombosis. Treated with intravenous unfractionated heparin and discharged home on warfarin, he returned a week later with extending thrombosis. Treatment with heparin followed by warfarin was reinitiated. Twenty-four hours following the readministration of warfarin, the patient's INR increased to 14.5. The platelet count dropped by more than 50%, and he developed venous limb gangrene of the left leg and skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…4,5 There are also case reports of warfarin-induced VLG complicating metastatic cancer, usually adenocarcinoma. [6][7][8][9][10] The clinical features and pathogenesis of this syndrome are obscure, although 2 reports 7,8 provided laboratory data (increased TAT to PC activity ratio) suggesting a model of disturbed procoagulant-anticoagulant balance mimicking that seen in HIT/warfarin-induced venous limb ischemia. We now report 10 patients with cancer-associated severe venous limb ischemia/gangrene allowing us to characterize the clinical and laboratory picture.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 There are also case reports of warfarin-induced VLG complicating metastatic cancer, usually adenocarcinoma. [6][7][8][9][10] The clinical features and pathogenesis of this syndrome are obscure, although 2 reports 7,8 provided laboratory data (increased TAT to PC activity ratio) suggesting a model of disturbed procoagulant-anticoagulant balance mimicking that seen in HIT/warfarin-induced venous limb ischemia. We now report 10 patients with cancer-associated severe venous limb ischemia/gangrene allowing us to characterize the clinical and laboratory picture.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the elevated INRs, these patients had higher levels of thrombin-antithrombin complexes simultaneously. Coagulation factor studies have revealed that these patients have severe depletion of factor VII (the coagulation factor most rapidly affected by vitamin K antagonists) as well as protein C. These observations suggest that patients with hypercoagulable disorders are predisposed to skin necrosis during anticoagulation administration due to an increase in the ratio of thrombin-antithrombin complexes to protein C activity (10, 11). …”
Section: Discussionmentioning
confidence: 99%
“…However, despite the elevated INRs, these patients simultaneously had higher levels of thrombin-antithrombin complexes (a marker of in vivo thrombin generation). Coagulation factor studies revealed that these patients experienced severe depletions of factor VII (the coagulation factor most rapidly affected by vitamin K antagonists) [15] as well as protein C. These observations suggest that patients with hypercoagulable disorders are predisposed to skin necrosis during anticoagulation administration due to an increase in the ratio of thrombin-antithrombin complexes to protein C activity [14, 16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…The alternative anticoagulant should not be stopped until the platelet count reaches a stable plateau and until there is at least 5 days of overlap with the INR >2 for 2 consecutive days [19]. In addition, excessive levels of warfarin anticoagulation should be avoided in hopes of preventing precipitous decrements in protein C levels [16, 17]. As was mentioned earlier, a supratherapeutic INR during warfarin initiation in a thrombophilic patient does not necessarily guarantee protection against thrombin generation.…”
Section: Discussionmentioning
confidence: 99%